Comparative Analysis of Islamic Commercial Bank Financial Performance Before and After the Emergence of Financial Technology - Shafia Jihadie, (ASEAN Journal of Halal Study, 2025)
Financial technology (fintech) has developed rapidly in recent years, especially in Indonesia. Fintech offers various product services, which greatly influence the performance of financial institutions, including sharia commercial bank finance. This research aims to find out how significant the differences are in the financial performance of Islamic commercial banks before and after the introduction of fintech. In this research, the author uses secondary data sourced from monthly Islamic commercial bank financial reports published by the Financial Services Authority (OJK) and uses a different test (paired sample t-test) for the analysis technique. The research results show that there was a significant difference between the risk indicators of Islamic Commercial Banks before and after the existence of fintech in Indonesia.